Prior Adjustment: An Extension of the Frisch-Waugh Theorem to the Method of Two-Stage Least Squares - J.C.R. Rowley (Queen's University, Department of Economics, 1970)
The problems of seasonal adjustment and other forms of prior adjustment have seldom been integrated into a general framework of estimation. A well-known result, due to Frisch and Waugh, has been used to demonstrate how linear seasonal influences might be treated in the context of the general linear statistical model. In this paper, the author establishes a proposition that one form of prior adjustment is consistent with two different estimating techniques that are in common use.
Keywords: 330